IL-27 Mediates Pro-Inflammatory Effects via the ERK Signaling Pathway During Preterm Labor - Huang, Dongni; Ran, Yuxin; Liu, Zheng; He, Jie; Yin, Nanlin; Qi, Hongbo (Frontiers in Immunology, 2021)
Preterm labor (PTL) is a multifactorial syndrome that results in birth prior to 37 weeks of gestation. However, the specific molecular mechanisms underlying this condition have yet to be elucidated. Previous research demonstrated that the abnormal expression of IL-27, and its receptors, played a role in the pathophysiology of preterm labor. In the present study, we established a Lipopolysaccharide (LPS)-stimulated, infection-induced, preterm mouse model based on wild-type C57BL/6 mice and WSX-1-/-C57BL/6 mice. WSX-1 knockdown led to a significant delay in birth by 11.32 ± 2.157h. In addition, compared with wild-type C57B/6 mice, the expression levels of IFN-γ, IL-1β, IL-6, TNF-α, and CXCL10, in the fetal membrane and myometrium of WSX-1-/-mice were significantly lower, particularly in the myometrium. We also confirmed similar pro-inflammatory effects arising from IL-27 in human amniotic cell line (WISH) and human myometrial smooth muscle cell line (HMSMC). Once stimulated by LPS, the pro-inflammatory action exhibited a synergistic effect and appeared to be time-dependent. Finally, we demonstrated that LY3214996, an inhibitor of the ERK pathway, significantly inhibited the pro-inflammatory effect mediated by IL-27. Overall, our data confirmed that the inflammatory effect mediated by the IL-27/IFN-r/ERK axis is involved in preterm labor. Our findings, therefore, provide an enhancement in our etiological understanding of the mechanisms underlying PTL.